THE ARCHITECTURE OF GHANSHYAM’S HOUSE: HERITAGE AND THE PRESENT - Rajkhowa, Arabinda; Buragohain, Nobin; Dutta, Munmi; Pegu, Khagen; Chutia, Ashim; Borah, Pubali (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The architectural monuments of the Ahom period constitute some of the most revered heritage sites of Assam. Among these, Ghanshyam’s House, located on the western bank of the Jayasagar tank in Sivasagar district, represents a structure of exceptional architectural and art-historical significance. Built by Ghanshyamuddin, a Muslim artisan from Kochbehar invited to the Ahom kingdom during the reign of Swargadeo Rudra Singha (r. 1696–1714 CE), the monument has received limited systematic scholarly attention. While some accounts suggest that Ghanshyam may have resided in this building, the present study argues, on the basis of architectural evidence and field investigation, that it functioned as a personal shrine constructed by the craftsman himself. The structure is distinguished by its synthesis of Ahom, Mughal, and Hindu architectural traditions, its distinctive terracotta sculptural programme, and its resemblance to the Gaudiya Matha style of Bengali Vaishnava temple architecture. This study analyses the architectural form, spatial organisation, sculptural iconography, and conservation status of this three-hundred-year-old monument, and evaluates its design in relation to the principles of Vastu Shastra. It is argued that formal recognition of its historical significance is essential to ensure this irreplaceable monument receives appropriate scholarly and institutional attention.